Fault Tolerant Control for an Over-Actuated WAM-V Catamaran. Issue 21 (2019) - Baldini, Alessandro; Felicetti, Riccardo; Freddi, Alessandro; Hasegawa, Kazuhiko; Monteriù, Andrea; Pandey, Jyotsna
Abstract: In this paper we propose a fault/failure tolerant control scheme for a catamaran with two azimuth thrusters. The scheme is based on a three level architecture: a heuristic-based control policy for proper reference generation, a control law for the vehicle dynamics to achieve speed tracking of the generated reference, and a control allocation level for optimally redistributing the control efforts among the thrusters even in presence of actuator faults and failures; finally, the low level control is invariant with respect to the fault/failure scenario, as well as the control law. The proposed architecture has been simulated considering the nonlinear model of a Wave Adaptive Modular Vessel catamaran, with the aim of tracking a reference expressed in waypoints, even when faults/failures affect one or more thrusters.